2021
DOI: 10.1007/s00167-021-06643-3
|View full text |Cite
|
Sign up to set email alerts
|

Over one third of patients with symptomatic femoroacetabular impingement display femoral or acetabular version abnormalities

Abstract: Purpose The aim of this study was investigate the relationship between version and torsional abnormalities of the acetabulum, femur and tibia in patients with symptomatic FAI. Methods A systematic review was performed according to PRISMA guidelines using the EMBASE, MEDLINE, PubMed and Cochrane databases. Original research articles evaluating the described version and torsional parameters in FAI were included. The MINORS criteria were used to appraise stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
0
9
1
Order By: Relevance
“…The reported frequency of patients with abnormal FV in FAI ranged from 13% 49 to 24% 50 for FV < 5°, and from 15% 50 to 34% 4 for FV > 20°. In comparison to a recent systematic review reporting abnormal FV of up to 51%, 17 a lower prevalence of patients with abnormal FV (45%; Table II ) was found. The reason for this discrepancy could be a selection bias of patients evaluated in an university hospital, or different measurement methods used in other studies.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…The reported frequency of patients with abnormal FV in FAI ranged from 13% 49 to 24% 50 for FV < 5°, and from 15% 50 to 34% 4 for FV > 20°. In comparison to a recent systematic review reporting abnormal FV of up to 51%, 17 a lower prevalence of patients with abnormal FV (45%; Table II ) was found. The reason for this discrepancy could be a selection bias of patients evaluated in an university hospital, or different measurement methods used in other studies.…”
Section: Discussioncontrasting
confidence: 92%
“…15 Another recent systematic review reported a frequency of abnormal FV of 51% in patients with symptomatic FAI. 17 In all the evaluated studies, they found a mean FV in the normal range (10° to 25°). For patients with cam-type FAI, they reported a frequency of femoral retroversion (FV < 10°) of up to 42%.…”
Section: Investigated Abnormalities Of Femoral Version (Fv) Femoral R...mentioning
confidence: 83%
See 2 more Smart Citations
“…The fact that reduced femoral antetorsion causes an early anterior conflict upon internal rotation of the hip has raised the significance of appreciating torsional correction in cases where cam and pincer correction alone would result in an inadequate restoration of internal rotation [ 6 ]. On the other hand, high femoral antetorsion has been described as being associated with posterior impingement and, in particular, extra-articular impingement between the femur and the ischium [ 7 ].…”
mentioning
confidence: 99%